2009
DOI: 10.1021/cm901149a
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Directing Effect of (S)-(−)-N-Benzylpyrrolidine-2-methanol and Benzylpyrrolidine in the Synthesis of STA-1: A New Computational Model for Structure Direction of Nanoporous Systems

Abstract: We propose a new computational model to study structure direction in nanoporous materials that takes into account the stability of the guest species in solution as well as the possibility of occluding solvent molecules in the nanopores. The model is applied to study the structure directing effect of (S)-(-)-N-benzylpyrrolidine-2-methanol (BPM) and benzylpyrrolidine (BP) in the synthesis of the nanoporous STA-1 material (SAO framework type), and compare results with experimental characterization. Despite the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The stabilization provided by the occlusion of the organic SDA (BP and BPM) and water molecules when directing the crystallization of the AFI and SAO structures has been discussed previously. , In these works, we proposed a new computational model to study structure direction in the synthesis of hydrophilic aluminophosphate frameworks. The nanopores of hydrophilic AlPO structures can in fact be occupied not only by the organic SDA molecules but also by water that is always present as solvent in hydrothermal syntheses; the contribution of water to the energy crystallization must therefore be taken into account.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stabilization provided by the occlusion of the organic SDA (BP and BPM) and water molecules when directing the crystallization of the AFI and SAO structures has been discussed previously. , In these works, we proposed a new computational model to study structure direction in the synthesis of hydrophilic aluminophosphate frameworks. The nanopores of hydrophilic AlPO structures can in fact be occupied not only by the organic SDA molecules but also by water that is always present as solvent in hydrothermal syntheses; the contribution of water to the energy crystallization must therefore be taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Our goal is to relate the supramolecular chemistry observed in the solutions with the mode of occlusion of the SDA molecules as monomeric or dimeric species within the AFI and SAO structures. We also employ a recently developed computational model for predicting the stabilization provided by the simultaneous occlusion of water molecules in the two frameworks , to determine the most stable arrangements of the guest (SDA and water) species within the structures and examine the effect of doping the AFI and SAO structures with Zn. The energetic balance that makes viable the crystallization of the two metastable AFI and SAO structures is examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently proposed a new computational model to study structure direction in the synthesis of hydrophilic aluminophosphate frameworks. , Previous results demonstrated that both the inclusion of water in the model as well as an energy term to account for the transfer of water and SDAs from the gel to the microporous frameworks are required for reliably modeling the main aspects of structure direction . Our computational protocol allows us to estimate the total internal energy of the system as a function of the ratio between SDA and water molecules inside the microporous framework.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Our computational protocol allows us to estimate the total internal energy of the system as a function of the ratio between SDA and water molecules inside the microporous framework. The net stabilization can be plotted as a function of the SDA content using the following equation (see refs and for details): Δ E stab-SDA false( n SDA false) = E f n SDA · false( E SDA vac + E SDA sol false) n H 2 O · false( E H 2 O vac + E H 2 O sol false) where E f refers to the internal energy of the AlPO framework containing the SDA and water molecules, n SDA and n H 2 O are the number of SDA and water molecules, respectively, E SDA vac and E H 2 O vac are the calculated energies of the molecules in vacuo, and E SDA sol and E H 2 O sol are the energies of the SDA and water in aqueous solution, which represent consistent estimations of the stability of the SDA and water molecules in the gel. Plotting the value of Δ E stab-SDA as a function of the number of SDA molecules ( n SDA ) enables us to estimate the most stable loading ratio of SDA and water molecules within the microporous frameworks, in equilibrium with their aqueous solution.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation